Real time IRIS recognition with FPGA based touch screen GUI / Mohd Shamimi Ibrahim - Ibrahim, Mohd Shamimi (2014)
Biometric identification provides special identification based on physical characteristic of a person. There are several types of biometric system for example, face, fingerprint, iris and signature. Every person has their own biometric trait that very tough to be stolen or duplicated. This unique characteristic can be recognized and extracted for the purpose of identification. Iris recognition technology determines the identity of an individual after capturing the person’s iris. The iris pattern was extracted and recognize, then it will be compared to database and identity of the individual determined. The objective of this work is to study the available techniques and reveals how the system can be applied in developing an iris recognition system using FPGA development board. This paper describes implementation of iris recognition with FPGA based GUI Touch Screen. User can interact with the system graphically using touch screen and control the processes which is part of the image processing of iris.